Old Testament Textual Criticism: A practical introduction - Brotzman, Ellis R. (Baker Academic, 2016)
This accessibly written, practical introduction to Old Testament textual criticism helps students understand the discipline and begin thinking through complex issues for themselves. The authors combine proven expertise in the classroom with cutting-edge work in Hebrew textual studies. This successful classic (nearly 25,000 copies sold) has been thoroughly expanded and updated to account for the many changes in the field over the past twenty years. It includes examples, illustrations, an updated bibliography, and a textual commentary on the book of Ruth.